2005
DOI: 10.1074/jbc.m411571200
|View full text |Cite
|
Sign up to set email alerts
|

Dystrophin Dp71 Expression Is Down-regulated during Myogenesis

Abstract: Dp71 expression is present in myoblasts but declines during myogenesis to avoid interfering with the function of dystrophin, the predominant Duchenne muscular dystrophy gene product in differentiated muscle fibers. To elucidate the transcriptional regulatory mechanisms operating on the developmentally regulated expression of Dp71, we analyzed the Dp71 expression and promoter activity during myogenesis of the C2C12 cells. We demonstrated that the cellular content of Dp71 transcript and protein decrease in myotu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
25
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 40 publications
(27 citation statements)
references
References 52 publications
2
25
0
Order By: Relevance
“…In myotubes, MyoD represses the expression of the Sp1 and Sp3 genes, and the resulting scarcity of these transcription factors causes down-regulation of the Dp71 promoter. In early myogenesis, Dp71 is expressed to participate in cytoskeletal remodelling [65]. Thus, the down-regulation of Sp1 suggests a crucial role for GTP in promoting differentiation.…”
Section: Discussionmentioning
confidence: 99%
“…In myotubes, MyoD represses the expression of the Sp1 and Sp3 genes, and the resulting scarcity of these transcription factors causes down-regulation of the Dp71 promoter. In early myogenesis, Dp71 is expressed to participate in cytoskeletal remodelling [65]. Thus, the down-regulation of Sp1 suggests a crucial role for GTP in promoting differentiation.…”
Section: Discussionmentioning
confidence: 99%
“…It was found that a 224-bp proximal promoter region containing four Sp1 binding sites and one activating protein 2 (AP2) element is necessary and sufficient for baseline expression of Dp71 in both muscular and neuronal cells. Furthermore, it was demonstrated that the proximal promoter region controls the repression of Dp71 expression that occurs during myogenesis, as well as promoter activity induction in differentiated neuronal cells [35,36]. In myoblasts, Sp1, together with specificity protein 3 (Sp3), transactivate the Dp71 promoter; however, Sp1 and −3 protein levels decrease during muscle cell differentiation, ultimately causing downregulation of the promoter in mature muscle cells [35] (Fig.…”
Section: Regulation Of Dp71 Expressionmentioning
confidence: 98%
“…Despite their different transcriptional functions, Sp1 and Sp3, generally compete for the same DNA-binding sites. In situ, several studies have demonstrated that both factors are associated to DNA-binding sites of a variety of promoters (53)(54)(55)(56)(57). They form homotypic and heterotypic complexes with numerous proteins, including other Sp family members (58 -60).…”
Section: Discussionmentioning
confidence: 99%